Correction: Co, Fe and N co-doped 1D assembly of hollow carbon nanoboxes for high-performance supercapacitors. Issue 3 (19th December 2022) - Kim, Minjun; Wang, Chaohai; Earnshaw, Jacob; Park, Teahoon; Amiralian, Nasim; Ashok, Aditya; Na, Jongbeom; Han, Minsu; Rowan, Alan E.; Li, Jiansheng; Yi, Jin Woo; Yamauchi, Yusuke
Abstract : Correction for 'Co, Fe and N co-doped 1D assembly of hollow carbon nanoboxes for high-performance supercapacitors' by Minjun Kim et al., J. Mater. Chem. A, 2022, 10, 24056–24063, ; https://doi.org/10.1039/D2TA06950D .